What is the prevalence, and what are the clinical correlates, of insulin resistance in young people presenting for mental health care? A cross-sectional study. Issue 5 (27th May 2019) - Scott, Elizabeth M; Carpenter, Joanne S; Iorfino, Frank; Cross, Shane P M; Hermens, Daniel F; Gehue, Jeanne; Wilson, Chloe; White, Django; Naismith, Sharon L; Guastella, Adam J; Hickie, Ian B
Abstract : Objectives: To report the distribution and predictors of insulin resistance (IR) in young people presenting to primary care-based mental health services. Design: Cross-sectional. Setting: Headspace-linked clinics operated by the Brain and Mind Centre of the University of Sydney. Participants: 768 young people (66% female, mean age 19.7±3.5, range 12–30 years). Main outcome measures: IR was estimated using the updated homeostatic model assessment (HOMA2-IR). Height and weight were collected from direct measurement or self-report for body mass index (BMI). Results: For BMI, 20.6% of the cohort were overweight and 10.2% were obese. However, <1% had an abnormally high fasting blood glucose (>6.9 mmol/L). By contrast, 9.9% had a HOMA2-IR score >2.0 (suggesting development of IR) and 11.7% (n=90) had a score between 1.5 and 2. Further, there was a positive correlation between BMI and HOMA2-IR (r=0.44, p<0.001). Participants in the upper third of HOMA2-IR scores are characterised by younger age, higher BMIs and depression as a primary diagnosis. HOMA2-IR was predicted by younger age (β=0.19, p<0.001) and higher BMI (β=0.49, p<0.001), together explaining 22% of the variance (F(2, 361) =52.1, p<0.001). Conclusions: Emerging IR is evident in a significant subgroup of young people presenting to primary care-based mental health services. While the major modifiable risk factor is BMI, a large proportion of the variance is not accounted for by other demographic, clinical or treatment factors. Given the early emergence of IR, secondary prevention interventions may need to commence prior to the development of full-threshold or major mood or psychotic disorders.